2010
DOI: 10.1007/s00216-010-4290-7
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun lipidomics for candidate biomarkers of urinary phospholipids in prostate cancer

Abstract: Qualitative and quantitative profiling of six different categories of urinary phospholipids (PLs) from patients with prostate cancer was performed to develop an analytical method for the discovery of candidate biomarkers by shotgun lipidomics method. Using nanoflow liquid chromatography-electrospray ionization-tandem mass spectrometry, we identified the molecular structures of a total of 70 PL molecules (21 phosphatidylcholines (PCs), 11 phosphatidylethanolamines (PEs), 17 phosphatidylserines (PSs), 11 phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(71 citation statements)
references
References 26 publications
3
66
1
1
Order By: Relevance
“…Increased level of PC in patients with prostate cancer is consistent with published data on the relative levels of PCs in samples of patients' plasma 23 and of PC in high-grade prostate cancer tissues. 32 In addition, 18:1/18:1-PC, 18:0/18:1-PC, and 18:0/ 20:4-PI were among the selected species found in our previous study to be significantly increased in patients with prostate cancer compared to healthy controls, 24 although experimental conditions in that study differed from those in the present one (see above).…”
Section: Resultscontrasting
confidence: 53%
See 1 more Smart Citation
“…Increased level of PC in patients with prostate cancer is consistent with published data on the relative levels of PCs in samples of patients' plasma 23 and of PC in high-grade prostate cancer tissues. 32 In addition, 18:1/18:1-PC, 18:0/18:1-PC, and 18:0/ 20:4-PI were among the selected species found in our previous study to be significantly increased in patients with prostate cancer compared to healthy controls, 24 although experimental conditions in that study differed from those in the present one (see above).…”
Section: Resultscontrasting
confidence: 53%
“…In an earlier study, we demonstrated the use of nLC-ESI-MS/MS in a semi-quantitative analysis of urinary PL species from 9 prostate cancer patients and 10 healthy control subjects. 24 That study identified 10 potential prostate cancer biomarkers, i.e., PL species showing greater than 3-fold difference in relative levels between patients and controls. In this study, several experimental conditions have been changed.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, previous publications demonstrated that the analysis of lipid extracts obtained from tumor human cells lines or human cancer biopsies showed increased levels of PC and/or PE ether lipids. In fact, these changes are correlated with malignancy and metastatic potential in various cancers [37][38][39][40][41][42]. Some studies demonstrated that plasmalogens are natural antioxidants, as the ether link is more prone to be oxidized than the double bonds usually found in many phospholipids in their fatty acid moiety [9,43].…”
Section: Resultsmentioning
confidence: 99%
“…[118] Elevated levels of sphingomyelin have also been reported to characterize human colon cancer, based on nuclear magnetic resonance (NMR) studies [119], whilst cancer cell motility was shown to be down-regulated by the interaction between CD9 and sialoglycosphingolipid GM3 using CRC cell lines [120] and ceramides have been found to induce apoptosis in CRC cell lines (HT-29, LOVO, and HCT-116). [121][122][123] Urinary phospholipids analysis using nanoflow LC-ESI MS/MS has been previously used for the analysis of breast [124,125]) and prostate cancer [124], but there is a dearth of literature on the application of this method to colorectal cancer. Interestingly though, urinary levels of metabolites of prostaglandin E 2 have been used as a biomarker for colorectal cancer risk evaluation.…”
Section: Lipidomicsmentioning
confidence: 99%